IN VITRO SCREENING OF ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL ANALYSIS OF PUNICA GRANATUM LINN. (FLOWERS) - KANNAIYAN MOORTHY,; THAMBIDURAI PUNITHA,; RAJA VINODHINI, (International Journal of Pharma and Bio Sciences, 2015)
The search for new substances with antimicrobial properties has become necessary due to the microbial capacity of resistance. Medicinal plants have become an important substitute since many plants exhibit antimicrobial activity. In this study, the ethanolic flower extracts of Punica granatum were assessed for their phytoconstituents and the antimicrobial property. A total of 21 microorganisms (19 bacteria and 2 fungi) were used for antimicrobial activity by disc diffusion method, broth dilution method and a standard procedure was employed to identify the Phytoconstituents. The Ethanolic flower extract showed significant inhibitory activity against Salmonella paratyphi A (25.6 mm), Salmonella typhimurium, Salmonella enterica (22.8 mm), Yersinia enterocolitica (22 mm), Staphylococcus epidermidis (21 mm), Salmonella brunei (20.6mm), Escherichia coli, Pseudomonas aeruginosa (20 mm) and Staphylococcus aureus, Burkholderia cepacia (19.6 mm) mean values were documented. Based on the broth dilution method, the ethanolic flower extract showed the MIC value 256µg/ml against Salmonella paratyphi A with a significant inhibitory activity. Ethanolic flower extract of P. granatum showed the highest antibacterial activity when compared to the antifungal activity could be due to the presence of some active phytoconstituents.